2007
DOI: 10.1002/elan.200703870
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of a Lignin Modified Electrode

Abstract: Alkali lignin undergoes strong adsorption on polycrystalline gold electrodes. Subsequent oxidation in a sulfuric acid solution leads to a restructured redox-active polymer that shows features characteristic for surface confined species. Surface coverage of up to 4.40 Â 10 À10 mol cm À2 may be obtained depending on the adsorption time or lignin concentration in the adsorption solution. Using Lavirons approach the electron-transfer rate constant and the transfer coefficient were found to be 8.9 s À1 and 0.35, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 22 publications
5
73
0
Order By: Relevance
“…The observed electrochemical activity of the KL-SiO 2 composite, especially that due to residual quinone moieties, point to the possibility of the application of such materials in electrochemical sensors for such applications as previously proposed [33,34,36].…”
Section: Electrochemical Characterisationsupporting
confidence: 53%
See 2 more Smart Citations
“…The observed electrochemical activity of the KL-SiO 2 composite, especially that due to residual quinone moieties, point to the possibility of the application of such materials in electrochemical sensors for such applications as previously proposed [33,34,36].…”
Section: Electrochemical Characterisationsupporting
confidence: 53%
“…It is noteworthy that with an increased amount of KL in the composite the cyclic voltammograms show a continuous increase in a reversible redox couple at the mean-peak potential of ca. 0.15 V, which can be attributed to the lignin-derived quinone moieties [1,[33][34][35][36].…”
Section: Electrochemical Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Papers are dedicated to the lignin oxidation on different electrodes for the sake of the development of a voltammetric lignin analysis method such as adsorption on polycrystalline gold electrodes 13 , Lignosulfonate modified glassy carbon electrode 14 , polypyrrole/lignin composite [15][16] , chloroaniline/lignin 17 have been discussed. This paper reports the successful preparation of composites modified electrode on glassy carbon electrode surface (LG/GCE, AHNSA/GCE, POPDA/ GCE, and its composite (LG-co-AHNSA and LGco-OPDA) by repetitive CV scans, to improve the electrochemical behavior of the prepared modified electrode by Cyclic voltammetry, Electrochemical Quartz Crystal Microbalance (EQCM) techniques and characterize with Fourier transform infrared spectroscopy (FTIR).…”
Section: Oriental Journal Of Chemistrymentioning
confidence: 99%
“…262 Other than the lignin-polypyrrole conjugated electrode, series of lignin-modifi ed electrodes were reported with showing high electrochemical activity and material stability. [269][270][271][272] As a none electrochemical applications of ligninpolyaniline composite, He et al recently reported that enzymatic hydrolysis lignin/polyaniline composite, which shows high-silverion adoption property on the composite surface. …”
Section: Polyaniline and Polypyrrolementioning
confidence: 99%